4. COMPARISON OF ANTIHYPERTENSIVE PREVENTION BETWEEN CONTINUOUS INTRAVENOUS INFUSION OF NORADRENALINE WITH PHENYLEPHRINE IN SPINAL BLOCK FOR CESAREAN SECTION IN NATIONAL HOSPITAL OF OBSTETRICS AND GYNECOLOGY (Vietnam Journal of Community Medicine, 2023)
Objective: To compare the antihypotensive prevention of continuous intravenous infusion ofnoradrenaline with phenylephrine in the spinal block for cesarean section. Subjects and researchmethods: Pregnant women with indications for cesarean section at the National Hospital of Obstetricsand Gynecology in 2022. Results: Mean age, mean height, and mean weight in the study of the twogroups were similar. All pregnant women in both groups showed loss of sensation at T10 (group N:2.75 ± 0.71, group P: 2.67 ± 0.85) and T6 (group N: 4.17 ± 0.81, group P: 4.22 ± 0.89) relativelyquickly, but the difference was not statistically significant with p>0.05. There was no difference inthe time of motor inhibition according to the average Bromage score (p>0.05). The blood pressurerate drops 20% - 30%: 2 cases in group N (6%) and group P 4 cases (8%). Conclusion: Continuousintravenous infusion of noradrenaline was comparable with continuous intravenous infusion ofphenylephrine in spinal anesthesia for cesarean section.
Keywords: Hypotension, cesarean section, noradrenaline, phenylephrine, National Hospital of Obstetrics and Gynecology.